Polycarbonate composition and preparation method thereof
Through the use of PC and COC composite and triazine light stabilizers and compatibility agents, the degradation problem of polycarbonate materials under UVC radiation is solved, the durability and electrical insulation of the material are improved, and it is suitable for medical supplies.
Patent Information
- Application Number
- CN202510105507.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-07-25
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and particularly relates to a polycarbonate composition and a preparation method thereof. Background Art
[0002] In the medical industry, UVC radiation disinfection is more efficient and environmentally friendly than traditional high-temperature disinfection or alcohol disinfection. It mainly relies on ultraviolet light with a wavelength of 200-275 nm, especially 250-270 nm, to damage the DNA or RNA structure of microorganisms to achieve the disinfection function. However, at present, the objects of UVC radiation disinfection are very limited because, compared with visible light, the photoaging degree of UVC is higher. Especially for some biodegradable organic substances dedicated to the medical field, such as polycarbonate, the irradiation degradation degree is high under the action of UVC. There will not only be obvious appearance color differences, but also some basic mechanical properties and flame retardancy will be reduced below the use standard in a short time. At the same time, as medical supplies, biodegradable organic substances are expected to achieve better mechanical strength and electrical properties during use, and avoid damage caused by external force or electrical breakdown and combustion during use, ultimately leading to safety accidents. Summary of the Invention
[0003] Based on the defects existing in the prior art, the purpose of the present invention is to provide a PC / COC composition. This product uses PC and COC compounding as the matrix resin system, and at the same time introduces triazine light stabilizers and composite compatibilizers as functional components, which can not only achieve good UVC irradiation resistance, but also have good impact strength and electrical properties, and can ensure the durability when applied to medical products.
[0004] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] A PC / COC composition, comprising the following components in parts by weight:
[0006] 50-80 parts of PC resin, 20-40 parts of COC copolymer, 0.1-1 part of light stabilizer, 0.5-2.5 parts of compatibilizer;
[0007] The light stabilizer is a triazine light stabilizer;
[0008] The compatibilizer includes glycidyl acrylate grafted polypropylene and ethylene-methyl acrylate copolymer.
[0009] COC copolymer is a cycloolefin copolymer obtained by copolymerizing norbornene monomer and ethylene monomer under the action of metallocene catalyst. This material has good dielectric properties and belongs to amorphous transparent material, so the birefringence is small. In theory, after compounding this component with PC resin, ideal dielectric properties and light resistance can be achieved. However, in actual application, the compatibility between PC resin and COC copolymer is poor. When compounding, it is not only difficult to fully exert the advantages of COC copolymer, and the product cannot achieve the effect of UVC irradiation resistance and thin-wall electrical insulation, but also the mechanical properties of the product will be weakened due to compatibility and dispersion problems. Therefore, in the technical solution of the present invention, in order to improve the compatibility of the two matrix organic substances and ensure that the product can achieve excellent UVC irradiation resistance, thin-wall electrical insulation and sufficient mechanical strength, a compatibilizer is formed by compounding a specific triazine light stabilizer and two specific components, namely glycidyl acrylate grafted polypropylene and ethylene-methyl acrylate copolymer. The former itself has a light absorption intensity of more than 18% at 254nm, and can achieve high synergistic light resistance, especially UVC irradiation effect after being combined with COC copolymer, improving the UVC irradiation resistance of the product. And glycidyl acrylate grafted polypropylene in the latter can directly react with the end groups of PC resin based on special functional groups, improving the compatibility between PC resin and COC copolymer. Ethylene-methyl acrylate copolymer is used as an auxiliary component of glycidyl acrylate grafted polypropylene to improve the compatibility between the two phases and between the matrix resin and functional additives, and at the same time it can also improve the mechanical toughness of the product and ensure the mechanical strength for use; under the action of the compatibilizer, COC copolymer can inhibit the damage of UVC irradiation to the molecular chain of PC resin, and at the same time can achieve ideal electrical insulation performance effect.
[0010] Preferably, in the PC / COC composition, the total mass content of PC resin and COC copolymer is ≥85%, more preferably 90%.
[0011] The PC / COC composition product of the present invention can achieve the expected technical effects with a relatively small amount of functional additives introduced, and has better controllability and operability when applied to subsequent processing by those skilled in the art. At the same time, the PC / COC composition of the present invention is not limited to the above types and contents of functional additives. Without affecting the technical effects of the product, those skilled in the art can also introduce other common PC-based or COC-based product additives according to actual needs.
[0012] Preferably, in the PC / COC composition, the weight parts of the PC resin are one of 50 parts, 55 parts, 58 parts, 60 parts, 62 parts, 65 parts, 68 parts, 70 parts, 75 parts, 80 parts or the range value of any two of them, more preferably 60 - 70 parts; the weight parts of the COC copolymer are one of 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts or the range value of any two of them, more preferably 25 - 35 parts; the weight parts of the light stabilizer are one of 0.1 part, 0.2 part, 0.5 part, 0.8 part, 1 part or the range value of any two of them, more preferably 0.5 - 0.8 parts; the weight parts of the compatibilizer are one of 0.5 part, 0.8 part, 1 part, 1.2 part, 1.5 part, 1.8 part, 2 part, 2.2 part, 2.5 part or the range value of any two of them, more preferably 1 - 2 parts.
[0013] Preferably, the melt flow rate of the PC resin at 260 °C and a load of 2.16 kg according to ISO 1133 - 2 - 2011 is 0.1 - 30 g / 10 min, and it can be at least one of bisphenol A type PC resin, bisphenol S type PC resin, and bisphenol F type PC resin.
[0014] Preferably, the melt flow rate of the PC resin at 260 °C and a load of 2.16 kg according to ISO 1133 - 2 - 2011 is 0.1 - 6 g / 10 min.
[0015] More preferably, the PC resin is bisphenol A type PC resin.
[0016] Preferably, the COC copolymer is a cycloolefin copolymer obtained by copolymerizing norbornene monomer and ethylene monomer under the action of a metallocene catalyst.
[0017] The COC copolymer described in the present invention can be prepared by a self - made method or can be an existing commercially available product.
[0018] More preferably, the melt flow rate of the COC copolymer at 260 °C and a load of 2.16 kg according to ISO 1133 - 2 - 2011 is 20 - 45 g / 10 min, and the density measured according to ASTM D792 - 2022 is 0.95 - 1.05 g / cm 3 .
[0019] Preferably, the triazine - type light stabilizers include but are not limited to at least one of triazine structures with substituent functional groups such as hydroxyphenyltriazine, methylphenyltriazine, and ethyloxytriazine.
[0020] Preferably, the glycidyl acrylate grafted polypropylene has a melt flow rate of 10 to 85 g / 10 min at 260 °C and a load of 2.16 kg according to ISO1133-2011;
[0021] More preferably, the glycidyl acrylate grafted polypropylene has a melt flow rate of 20 to 30 g / 10 min at 260 °C and a load of 2.16 kg.
[0022] The melt fluidity of the glycidyl acrylate grafted polypropylene affects its dispersibility in the product and the degree of modification of the PC resin. When the melt flow rate of the glycidyl acrylate grafted polypropylene is preferably within the above range, the toughness and CTI performance of the product are better.
[0023] Preferably, the grafting rate of the glycidyl acrylate grafted polypropylene is 0.05 to 2.5%;
[0024] More preferably, the grafting rate of the glycidyl acrylate grafted polypropylene is 0.7 to 1.2%.
[0025] At a lower grafting rate, glycidyl acrylate will slightly promote the degradation of polypropylene, thereby increasing the fluidity of the polypropylene resin. As the grafting rate of the glycidyl acrylate grafted polypropylene increases, the material fluidity is also affected, which in turn leads to a change in the degree of charge accumulation of the product in a wet high-voltage electrical environment, and the CTI performance of the product changes; at the same time, its grafting rate also affects the compatibility of the two-phase matrix of the alloy, and the toughness and radiation resistance stability of the product are also affected.
[0026] The glycidyl acrylate group will react with the terminal hydroxyl group of the PC resin. After grafting, the PP matrix and the COC second monomer have good compatibility, and through dual effects, it helps the product achieve component compatibility and UVC radiation resistance. When the grafting rate of the glycidyl acrylate grafted polypropylene is preferably within the above range, the comprehensive performance of the product is better.
[0027] The grafting rate of the glycidyl acrylate grafted polypropylene can be measured by infrared spectroscopy: using a Fourier transform infrared spectrometer to test a sample with a fixed thickness to obtain the characteristic absorption peaks of the infrared spectrum, and the grafting rate can be calculated by comparing the ratio of the absorbance intensities of the epoxy groups.
[0028] It should be noted that the glycidyl acrylate grafted polypropylene described in the present invention can be obtained by a self-made method or directly used as a commercially available product. When choosing to make it by oneself, the following method can be used for preparation:
[0029] Using glycidyl acrylate as a monomer and melt-extruding and grafting it with polypropylene resin, the glycidyl acrylate grafted polypropylene is obtained.
[0030] That is, the component can be obtained by melt extrusion grafting of glycidyl acrylate and polypropylene resin.
[0031] Specifically, the mass ratio of glycidyl acrylate to polypropylene resin is (1 - 2.5):(97.5 - 100).
[0032] Specifically, the melt extrusion grafting process can be directly carried out by a screw extruder. Specifically, set the screw extruder to the target temperature, then add glycidyl acrylate and polypropylene resin into the feed port for mixing, melt extrusion grafting, and the product is obtained.
[0033] In addition, those skilled in the art can also add various processing aids including but not limited to initiators, lubricants, dispersants, etc. in this process according to common knowledge and processing effects, as long as the grafting rate and fluidity of the substance are not affected, which are not elaborated one by one here.
[0034] Specifically, the temperature of the melt extrusion grafting is ≥190 °C.
[0035] More specifically, the melt flow rate of the polypropylene resin at 260 °C and a load of 2.16 kg according to ISO1133 - 2011 is 10 - 90 g / 10 min.
[0036] Preferably, the molar ratio of ethylene monomer to methyl acrylate monomer in the ethylene - methyl acrylate copolymer is (9.5:0.5) - (7:3).
[0037] Preferably, in the compatibilizer, the melt flow rate of the ethylene - methyl acrylate copolymer at 190 °C and a load of 2.16 kg is 0.1 - 1 g / 10 min.
[0038] Preferably, in the compatibilizer, the mass ratio of glycidyl acrylate - grafted polypropylene to ethylene - methyl acrylate copolymer is (0.5 - 4):1.
[0039] More preferably, in the compatibilizer, the mass ratio of glycidyl acrylate - grafted polypropylene to ethylene - methyl acrylate copolymer is (1 - 3):1.
[0040] As the component mainly optimizing the compatibility of the COC copolymer in the PC resin, when the relative addition amount of glycidyl acrylate - grafted polypropylene is relatively large, the comprehensive performance of the product is better. Especially when the two components are preferably within the above - mentioned ranges, the UVC irradiation resistance performance of the product is not only better, but also the toughness of the product can reach a relatively high level.
[0041] Preferably, the PC / COC composition further comprises 0.1 - 5 parts of functional aids or processing aids;
[0042] Further preferably, the functional aids include, but are not limited to, at least one of a dripping inhibitor, an antistatic agent, and an antibacterial agent, and the processing aids include at least one of a chain extender, a lubricant, and a demolding agent. Those skilled in the art can add various different functional aids or processing aids according to actual needs without affecting the expected performance of the products of the present invention. For example, in order to make the products also have antistatic properties during application, those skilled in the art can add an antistatic agent to the products; in order to make the demolding effect of the products better during processing, those skilled in the art can add a small amount of lubricant or demolding agent to lubricate.
[0043] Another object of the present invention also lies in providing a preparation method of the PC / COC composition, comprising the following steps:
[0044] Adding each component into a screw extruder for melt extrusion and pelletizing to obtain the PC / COC composition.
[0045] Preferably, the temperature zones of the screw extruder are set as follows: zone 1: 230 - 250 °C, zone 2: 230 - 260 °C, zone 3: 230 - 250 °C, zone 4: 240 - 260 °C, zone 5: 240 - 260 °C, zone 6: 240 - 260 °C, zone 7: 250 - 260 °C, zone 8: 250 - 260 °C, zone 9: 240 - 260 °C, zone 10: 240 - 260 °C, the screw rotation speed is 300 - 500 rpm, and the screw length-diameter ratio is (45 - 50):1.
[0046] The preparation method of the PC / COC composition of the present invention is simple, has low requirements for equipment, and can realize industrial-scale production.
[0047] Another object of the present invention lies in providing an application of the PC / COC composition in the preparation of medical supplies.
[0048] More preferably, the medical supplies include medical device housings, wearable medical devices, injection systems, and surgical peripheral components.
[0049] Another object of the present invention lies in providing a medical supply, which comprises the PC / COC composition of the present invention.
[0050] Based on the combination of the COC copolymer, the specific compatibilizer, and the auxiliary effect of the light stabilizer, the PC / COC composition of the present invention can not only achieve good UVC irradiation resistance, but also achieve excellent mechanical impact resistance and thin-wall electrical insulation, and is very suitable for medical supplies with high requirements for these properties.
[0051] The beneficial effects of the present invention are as follows. The present invention provides a PC / COC composition, which uses a PC and COC blend as the matrix resin system, and at the same time introduces triazine light stabilizers and a composite compatibilizer as functional components. It can not only achieve good UVC irradiation resistance performance, but also has good impact strength and electrical properties, ensuring durability when applied to medical products. Detailed Embodiments
[0052] To better illustrate the purpose, technical solutions, and advantages of the present invention, the present invention will be further described below in conjunction with specific examples and comparative examples. The purpose is to understand the content of the present invention in detail, rather than limiting the present invention. All other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention are all common ordinary reagents and instruments unless otherwise specified.
[0053] Examples 1 - 13
[0054] Embodiments of the PC / COC composition and its preparation method of the present invention. The component composition of the PC / COC composition is shown in Table 1.
[0055] The preparation method of the PC / COC composition includes the following steps:
[0056] Mix all components evenly, and then melt - extrude and pelletize in a twin - screw extruder to obtain the PC / COC composition.
[0057] When the components are melt - extruded, the temperature zones of the screw extruder are set as Zone 1: 240 °C, Zone 2: 250 °C, Zone 3: 250 °C, Zone 4: 250 °C, Zone 5: 250 °C, Zone 6: 250 °C, Zone 7: 255 °C, Zone 8: 255 °C, Zone 9: 255 °C, Zone 10: 255 °C. The screw speed is 500 rpm, and the screw length - to - diameter ratio is 48:1.
[0058] Comparative Examples 1 - 8
[0059] The difference between each comparative example and the example lies only in the types and ratios of the components, as shown in Table 2.
[0060] Among the components of each example and comparative example,
[0061] The PC resin 1 is PC2070 produced by Wanhua Chemical, and its melt flow rate at 300 °C and 1.2 kg load is 6.5 g / 10 min;
[0062] The PC resin 2 is PC2100 produced by Wanhua Chemical, and its melt flow rate at 300 °C and 1.2 kg load is 9 g / 10 min;
[0063] The compatibilizer 1 is glycidyl acrylate grafted polypropylene with a grafting rate of 0.80%, and its melt flow rate at 260°C and a load of 2.16 kg is 25.8 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0064] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 1:99 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190°C; the polypropylene resin is EP-548 produced by KINGFA, and its melt flow rate at 260°C and a load of 2.16 kg is 20.8 g / 10 min;
[0065] The compatibilizer 2 is glycidyl acrylate grafted polypropylene with a grafting rate of 1.00%, and its melt flow rate at 260°C and a load of 2.16 kg is 22.5 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0066] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 1.5:98.5 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190°C; the polypropylene resin is EP-548 produced by KINGFA, and its melt flow rate at 260°C and a load of 2.16 kg is 20.8 g / 10 min;
[0067] The compatibilizer 3 is glycidyl acrylate grafted polypropylene with a grafting rate of 0.13%, and its melt flow rate at 260°C and a load of 2.16 kg is 23.8 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0068] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 1:100 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190°C; the polypropylene resin is EP-548 produced by KINGFA, and its melt flow rate at 260°C and a load of 2.16 kg is 20.8 g / 10 min;
[0069] The compatibilizer 4 is glycidyl acrylate grafted polypropylene with a grafting rate of 2.33%, and its melt flow rate at 260°C and a load of 2.16 kg is 18.3 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0070] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 2.5:97.5 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190°C; the polypropylene resin is EP-548 produced by KINGFA, and its melt flow rate at 260°C and a load of 2.16 kg is 20.8 g / 10 min;
[0071] The compatibilizer 5 is glycidyl acrylate grafted polypropylene with a grafting rate of 0.75%, and its melt flow rate at 260 °C under a load of 2.16 kg is 24.3 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0072] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 1:99 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190 °C; the polypropylene resin is Z30S produced by KINGFA, and its melt flow rate at 260 °C under a load of 2.16 kg is 21.5 g / 10 min;
[0073] The compatibilizer 6 is glycidyl acrylate grafted polypropylene with a grafting rate of 0.82%, and its melt flow rate at 260 °C under a load of 2.16 kg is 12.5 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0074] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 1:99 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190 °C; the polypropylene resin is T30S produced by KINGFA, and its melt flow rate at 260 °C under a load of 2.16 kg is 11.8 g / 10 min;
[0075] The compatibilizer 7 is glycidyl acrylate grafted polypropylene with a grafting rate of 0.81%, and its melt flow rate at 260 °C under a load of 2.16 kg is 84.8 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0076] Mix glycidyl acrylate and polypropylene resin in a mass ratio of 1:99 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 190 °C; the polypropylene resin is BM610 produced by KINGFA, and its melt flow rate at 260 °C under a load of 2.16 kg is 83.6 g / 10 min;
[0077] The compatibilizer 8 is maleic anhydride grafted polypropylene with a grafting rate of 0.84%, and its melt flow rate at 260 °C under a load of 2.16 kg is 23.5 g / 10 min. It is a self-made product, and the preparation method is as follows:
[0078] Mix maleic anhydride and polypropylene resin in a mass ratio of 1:99 and feed them into a screw extruder for melt extrusion, and set the melting temperature at 200 °C; the polypropylene resin is EP-548 produced by KINGFA, and its melt flow rate at 260 °C under a load of 2.16 kg is 20.8 g / 10 min;
[0079] The compatibilizer 9 is polypropylene resin B8101 produced by Sinopec;
[0080] The compatibilizer 10 is AC1125 produced by Dow, ethylene-methyl acrylate copolymer;
[0081] The compatibilizer 11 is 5110G produced by Dow, a polyethylene resin;
[0082] The compatibilizer 12 is PTW produced by Dow, ethylene-propylene-methyl acrylate terpolymer;
[0083] The compatibilizer 13 is SAG-002 produced by Jiayirong, epoxy-grafted SAN;
[0084] The COC copolymer is ALP5014 produced by Mitsui of Japan;
[0085] The light stabilizer 1 is 5577 produced by Qitai, China Taiwan, a triazine light stabilizer;
[0086] The light stabilizer 2 is 1164 produced by Lianlong, a triazine light stabilizer;
[0087] The light stabilizer 3 is 5411 produced by Qitai, Taiwan, China, a benzotriazole light stabilizer.
[0088] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.
[0089] Table 1
[0090]
[0091]
[0092] Table 2
[0093]
[0094] In order to verify the performance of the PC / COC composition of the present invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, and the specific steps are as follows:
[0095] (1) UVC irradiation resistance test: The tensile strength A0 of the product was tested according to ASTM D638-2018, and the test was carried out under the condition of a tensile rate of 10 mm / min; then, the parallel samples were irradiated with 253.7 nm (50 W) UVC for 1000 h in an environment of 50% relative humidity and 25°C, and each sample was subjected to the same test as above;
[0096] (2) Notched impact strength test: Tested according to ASTM D256-2010 standard, with a thickness of 3.2 mm, V-notch was used for testing, the impact energy was 1.25 J, and it was pre-conditioned in an environment of 23 °C / 50% relative humidity for 72 h before testing.
[0097] (3) CTI test: Tested according to ASTM D3638-2007 standard.
[0098] The test results are shown in Tables 3 and 4.
[0099] Table 3
[0100]
[0101] Table 4
[0102]
[0103] It can be seen from Tables 3 and 4 that the PC / COC composition described in the present invention has ideal UVC irradiation resistance performance, and at the same time, the impact resistance performance and CTI electrical insulation performance are also relatively high. Specifically, the tensile strength retention rate of the product can still remain above 90% after long-term UVC irradiation (because when UVC irradiation causes photodegradation of the product, it will also promote partial cross-linking reaction of polycarbonate, so in the case of the product having irradiation resistance, the tensile strength retention rate will be higher than 100%), and the notched impact strength of the product can reach 500 J / m 2 Above, each product has passed the CTI test under 600 V voltage.
[0104] In contrast, the products described in Comparative Examples 1 and 2 did not introduce glycidyl acrylate grafted polypropylene or ethylene-methyl acrylate copolymer as compatibilizer components, and the compatibility problem between PC and COC could not be improved. The products could not achieve good irradiation resistance performance and CTI performance, and the toughness of the products was relatively low. Especially in the case of lacking the latter, the notched impact strength of the product in Comparative Example 1 could not reach 200 J / m 2Above. On the other hand, if any one of the two compatibilizers is replaced by other types of compatibilizer components, as shown in Comparative Examples 3-6 and 8, in addition to the toughness of the product not being guaranteed to meet the standard, it may even occur that the tensile strength retention rate after UVC irradiation is worse than that of the blank products in Comparative Example 1 or 2, that is, these compatibilizers even have a negative effect on the radiation resistance performance of the product. In Comparative Example 5, polyethylene resin is used as a compatibilizer for compounding, and the CTI performance of the product is further weakened, indicating that the combination of the two compatibilizers in the product of the present invention has specificity. Further, when the two are combined, as can be seen from Examples 1 and 10-12, when the mass ratio of glycidyl acrylate grafted polypropylene to ethylene-methyl acrylate copolymer is (1-3):1, not only is the toughness of the product higher, but also the UVC radiation resistance performance is further improved.
[0105] In the product of the present invention, the triazine light stabilizer has a light absorption intensity of more than 18% at 254 nm, which can greatly improve the UVC radiation resistance performance of the product and maintain the better CTI performance of the product. If the light stabilizer used is not of this type, as shown in Comparative Example 7, not only can the radiation resistance performance not reach the qualified level, but also the electrical performance of the product will be affected and the CTI will not meet the standard.
[0106] It can be seen from Example 1 and Examples 4-9 that the grafting rate of glycidyl acrylate grafted polypropylene and the melt index of the corresponding polypropylene resin itself will affect the fluidity, and thus affect the radiation resistance performance, toughness and CTI performance of the product, but they are all better than those of the products in each comparative example.
[0107] Finally, it should be noted that the above examples are only used to illustrate the technical solutions of the present invention and not to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A PC / COC composition, characterized in that, Comprising the following components in parts by weight: 50 - 80 parts of PC resin, 20 - 40 parts of COC copolymer, 0.1 - 1 part of light stabilizer, 0.5 - 2.5 parts of compatibilizer; The light stabilizer is a triazine - type light stabilizer; The compatibilizer includes glycidyl acrylate - grafted polypropylene and ethylene - methyl acrylate copolymer.
2. The PC / COC composition according to claim 1, wherein The melt flow rate of the PC resin at 260 °C and a load of 2.16 kg is 0.1 - 30 g / 10 min.
3. The PC / COC composition according to claim 1, wherein The COC copolymer is a cycloolefin copolymer obtained by copolymerizing norbornene monomer and ethylene monomer under the action of a metallocene catalyst.
4. The PC / COC composition according to claim 1, wherein The triazine - type light stabilizer includes at least one of hydroxyphenyl triazine, methylphenyl triazine, and ethyloxy triazine.
5. The PC / COC composition according to claim 1, characterized in that, The melt flow rate of the glycidyl acrylate - grafted polypropylene at 260 °C and a load of 2.16 kg is 10 - 85 g / 10 min, and / or the melt flow rate of the ethylene - methyl acrylate copolymer at 190 °C and a load of 2.16 kg is 0.1 - 1 g / 10 min.
6. The PC / COC composition according to claim 1, characterized in that, The grafting rate of the glycidyl acrylate - grafted polypropylene is 0.05 - 2.5%.
7. The PC / COC composition according to claim 1, characterized in that, In the compatibilizer, the mass ratio of glycidyl acrylate - grafted polypropylene to ethylene - methyl acrylate copolymer is (0.5 - 4):
1.
8. The preparation method of the PC / COC composition according to any one of claims 1 to 7, characterized in that, Comprising the following steps: Adding each component into a screw extruder for melt extrusion granulation to obtain the PC / COC composition.
9. Use of the PC / COC composition according to any one of claims 1 - 7 in the preparation of medical supplies; preferably, the medical supplies include medical device housings, wearable medical devices, injection systems, and surgical peripherals.
10. A medical supply, characterized in that, Comprising the PC / COC composition according to any one of claims 1 - 7.